SISTEM DINAMIK KETERSEDIAAN KEDELAI DALAM RANGKA SWASEMBADA PANGAN DI PROVINSI BALI - Linda Krisdayanti, Ni Made; Satriawan, I K.; Sedana Yoga, I W.G. (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2017)
The objectives of this research were to determine the factors that affect the availability of soybean, to arrange modelling system dynamic of soybean availability, to calculate the availability of soybean in an effort to achieve food self-sufficiency, to arrange alternative recommendation of plausible scenario to fulfil the food self-sufficiency of soybean in Bali. This research were conducted in Bali on March to June 2017. The step of this research were determine the location of research, identification the problem and purpose, conceptualization of system, formulation of model, verification and validation of model, simulation with scenario and arrange alternative of recommendation. The factors that influence of availability of soybean in Bali such as the area of planting, harvested area, the production of soybean, inter island trading, harvested productivity, area productivity, intensification of technology, ekstensification rate, land conversion rate, population growth, migration net, requirement of tempe and tofu industry, requirement of soybean milk industry, requirement of soybean snack. Dynamic model of availability soybean that had simulation with few scenarios was increased of soybean production with improvement efforts of the area of planting and increased of productivity in intensification technology effort. Availability of soybean in Bali was decreased of productivity, the are of planting, harvested area, and productivity.. Alternative recommendation of subtlety scenario to fulfill the requirement of soybean in Bali which were expected to be applied with empowerment area scenario was 15% every year and the soybean’s area of planting, and increased productivity with effort intensification from 1,35 ton/ha become 2,94 ton/ha. Key words: system dynamic, availabilit y of soybean, simulation, Bali